Solar radiation model and optimization of asymmetric large-span externally insulated plastic greenhouses - Chuanqing Wang; Kai Liu; Hongyu Ma; Tianhua Li; Shaojie Wang; Dalong Zhang; Min Wei (PLoS ONE, 2025)
To improve the light environment of asymmetric large-span externally insulated plastic greenhouses, a solar radiation model that considers the projection path equations of the insulation quilts and validated the model was established. The model was employed to investigate the impact of different heights, spans, and north lighting projection lengths on the greenhouses’ light environment. The results revealed that ground radiation interception, a key component of winter lighting, was most influenced by height, followed by span, and least influenced by the projection length of the north lighting roof. Additionally, ground radiation spatial uniformity was most affected by height, followed by the projection length of the north lighting roof, and least influenced by span. The optimization objectives for solar radiation were set to maximize solar radiation interception and minimize the coefficient of variation. The optimal structural parameters for the asymmetric large-span externally insulated plastic greenhouse were determined using the NSGA-II method and the entropy weight-TOPSIS method: the height of 6.97 m, and the projection length of north lighting roof is 7.44 m for a greenhouse with a span of 20.00 m. Compared to the initial greenhouse, the optimized design enhances both radiation interception performance and ensures uniform light distribution. These results offer valuable theoretical guidance for greenhouse construction.